Cytotoxicity, In vitro anti-Leishmanial and fingerprint HPLC- photodiode array analysis of the roots of Trillium govanianum. Issue 18 (17th September 2018) - Khan, Kashif Maqbool; Nahar, Lutfun; Mannan, Abdul; Ul-Haq, Ihsan; Arfan, Muhammad; Ali Khan, Ghazanfar; Hussain, Izhar; Sarker, Satyajit D.
Abstract: Trillium govanianum Wall. ex D. Don (Melanthiaceae alt. Trilliaceae), commonly known as 'nagchhatry' or 'teen patra', distributed from Pakistan to Bhutan about 2500–3800 m altitude is indigenous to Himalayas region. In folk medicine the plant has been reported for the treatment of wound healing, sepsis and in various sexual disorders . This paper reports, for the first time, to evaluate the cytotoxicity, in vitro anti-leishmanial (promastigotes) and fingerprint HPLC-photodiode array analysis of the MeOH extract of the roots of T. govanianum and its solid phase extraction fractions. Reverse phase HPLC-PDA based quantification revealed the presence of significant amount of quercetin, myrecetin and kaemferol ranging from 0.221to 0.528 μg/mg DW. MeOH extract revealed distinguishable protein kinase inhibitory activity against Streptomyces 85E strain with 18 mm bald phenotype. The remarkable toxicity profile against brine shrimps and leishmanial was manifested by MeOH extract with LC50 10 and 38.5 μg/mL, respectively. Abstract :